2021
DOI: 10.18280/ts.380421
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Classification Using Squeeze and Excitation Convolutional Neural Networks with Grad Cam++ Class Activation Function

Abstract: The leading cause of cancer-related death globally has been identified as lung cancer. Early lung nodule detection is critical for lung cancer therapy and patient survival. The Gard Cam++ Class Activation Function is used with a squeeze-and-excite network to provide a revolutionary method for differentiating malignant from benign lung nodules on CT scans. The new SENET (Squeeze-and-Excitation Networks) Grad Cam++ module, which combines the features calibration and discrimination benefits of SENET, has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The research uses Grad-CAM++ with the Mask Regional Convolution Neural Network, which has shown a powerful real-time ability to detect and classify existing objects and shapes [24]. The research uses Grad-CAM++ enabled with the squeeze-and-excite network on the CT scan dataset of lung cancer [25]. The research improves Grad-CAM++ to activate the 3D CNN layer to classify lung nodules and detect lung cancer early [26].…”
Section: Related Workmentioning
confidence: 99%
“…The research uses Grad-CAM++ with the Mask Regional Convolution Neural Network, which has shown a powerful real-time ability to detect and classify existing objects and shapes [24]. The research uses Grad-CAM++ enabled with the squeeze-and-excite network on the CT scan dataset of lung cancer [25]. The research improves Grad-CAM++ to activate the 3D CNN layer to classify lung nodules and detect lung cancer early [26].…”
Section: Related Workmentioning
confidence: 99%
“…A previous study developed a secure data share method based on dynamic groups to carry out key distribution and data sharing [6]. A secure data-sharing mechanism is first created to share the key securely without using a communication channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SHAP was then used to highlight red areas that minimize the probability of the tumor. maximize the probability of a tumor and green areas that mi Joshua et al 80 presented a paper on lung cancer classification using CT images. The paper proposed using a squeeze‐and‐excite network and GradCAM++ to classify malignant and benign lung nodules on CT scans.…”
Section: Related Workmentioning
confidence: 99%